Pharmacoeconomic analysis of the use of a fixed combination of tiotropium bromide and olodaterol as maintenance therapy in patients with chronic obstructive pulmonary disease in the Russian Federation - S. К. Zyryanov; I. N. Dyakov (Фармакоэкономика, 2022)
Objective: to evaluate the pharmacoeconomic effectiveness of the use of a fixed double combination of tiotropium bromide + olodаterol in order to treat chronic obstructive pulmonary disease (COPD) in comparison with less expensive monotherapy with long-acting beta-2-agonists (LABA) or long-acting anticholinergics (LAAC) with its insufficient effectiveness.Material and methods. The analysis of the impact on the health care system budget of the use of a fixed double chemical combination was carried out. The combination used was the one of tiotropium bromide + olodаterol in patients suffering from COPD who do not achieve effective disease control during LABA or LAAC monotherapy. We used published data on the distribution of patients into groups according to the classification of the Global Initiative for Chronic Obstructive Lung Disease (GOLD), also according to the therapy used and the frequency of exacerbations with hospitalization, obtained in a Russian epidemiological study. Direct and indirect costs associated with basic therapy and treatment of exacerbations requiring hospitalization were estimated as well.Results. Previously, it was shown that about 21.8% of patients with GOLD D severity of COPD receive therapy of insufficient efficacy (LABA monotherapy or long-acting M-cholinolytics). The use of a fixed combination of tiotropium bromide + olodaterol in such patients instead of monotherapy will reduce the direct costs of hospitalization by 21.1%, and the total costs (direct and indirect) – by 4.6%. On the scale of the Russian Federation, this will save 17.2 billion rubles a year.Conclusion. The results obtained showed that, despite the reasonably high cost of a fixed double combination in comparison with monopreparations, the use of double bronchodilating therapy allows to achieve more effective treatment and reduces both direct medical costs associated with hospitalization of patients with exacerbations of COPD, and direct non-medical and indirect costs associated with absenteeism of patients to work due to temporary disability as a result of hospitalization.